Nine Billion Branches: A Digital Poem by Jason Nelson—the Home of Objects - Ostalska, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2024)
In his digital poem Nine Billion Branches, Jason Nelson explores various modes of belonging, which could be realized multifacetedly on corporeal, social, political, aesthetic and ecological levels. These locations range from the domestic (i.e. the bedroom, garage or living room) to the more abstract, such as the human body and language. The intricate network of relations between digital objects (rendered in the poem via a map of hypertextual links and limited interactivity) is expressed by means of kaleidoscopic, co-ordinate and not causal-effect connections. The article studies the notion of digital objects in Nelson’s poem, showing how the online milieu affects the reading and interpretation processes. In this context, digital hermeneutics comes into focus, especially as regards visualizations. When discussing the selected poetic titles (their total number is 40), the article explores Harman’s Object-Oriented Ontology, linking it to digitality. The article aims to analyze how following the digital paths in Nine Billion Branches, belonging to the world, to language, one’s body and locations can be perceived as a shifting web of interactions between the digital objects and readers/players, in the everchanging text that has no beginning or end.